2020
DOI: 10.3390/jcm9103159
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Sacubitril/Valsartan on the Right Ventricular Arterial Coupling in Patients with Heart Failure with Reduced Ejection Fraction

Abstract: Background: right ventricle-pulmonary artery (RV-PA) coupling assessed by measuring the tricuspid anular plane systolic excursion (TAPSE)/pulmonary artery systolic pressure (PASP) ratio has been recently proposed as an early marker of right ventricular dysfunction in patients with heart failure with a reduced ejection fraction (HFrEF). Methods: As the effects of sacubitril/valsartan therapy on RV-PA coupling remain unknown, this study aimed to analyse the effect of this drug on TAPSE/PASP in patients with HFrE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(38 citation statements)
references
References 40 publications
(33 reference statements)
6
32
0
Order By: Relevance
“…At baseline, 97.46% were treated with ACE inhibitors or sartans, 83.9% with beta‐blockers (median heart rate of 70 b.p.m. ), and 64.41% with mineralocorticoid receptor antagonist, as in previous reports 29–33 . After SV initiation, NT‐proBNP values decreased by 30% or more in 51.72% of the whole population (a threshold considered as clinically significant 22,34 ), which is near the 46.3% reported by Pharithi et al 35 .…”
Section: Discussionsupporting
confidence: 78%
“…At baseline, 97.46% were treated with ACE inhibitors or sartans, 83.9% with beta‐blockers (median heart rate of 70 b.p.m. ), and 64.41% with mineralocorticoid receptor antagonist, as in previous reports 29–33 . After SV initiation, NT‐proBNP values decreased by 30% or more in 51.72% of the whole population (a threshold considered as clinically significant 22,34 ), which is near the 46.3% reported by Pharithi et al 35 .…”
Section: Discussionsupporting
confidence: 78%
“…Our results that sacubitril/valsartan independently improved RV function seem to be consistent with those of other small-scale studies. 20,21 Our findings suggest that the inhibitory effects of sacubitril/valsartan on the neprilysin and renin–angiotensin–aldosterone system activity might directly improve RV function, not just by compensatory effects through improvements in the LV pulmonary circulation. Clements et al 24 observed that RV function indicators significantly improved in a rat model of pulmonary hypertension after 6 weeks of sacubitril/valsartan treatment.…”
Section: Discussionmentioning
confidence: 78%
“…Some real-world studies have reported similar results regarding the benefits of sacubitril/valsartan on RV function. Masarone et al 20 demonstrated substantial TAPSE improvements after long-term sacubitril/valsartan treatment in patients with HFrEF during 1-year follow-up, and these improvements persisted after 2 years. In a previous observational cohort in Italy, the mean TAPSE significantly increased from 7.8 ± 3.9 mm at baseline to 16.5 ± 4.0 mm after 1-year treatment ( P < 0.001).…”
Section: Discussionmentioning
confidence: 97%
“…The gold standard for determining RV-PA coupling consists of the ratio between RV end-systolic elastance and effective arterial elastance [Ees/Ea] [ 17 , 26 ], which requires invasive measurements by means of a RHC as well as specific, dedicated material and is thus, rarely employed in clinical practice. Recently, the TAPSE/PASP ratio has been proposed as a non-invasive indicator of RV to PA coupling [ 19 , 20 , 21 , 22 , 27 ]. This index provides a valuable non-invasive measure of RV contractile state and RV load adaptability beyond the information afforded by each separate variable as an index of changes in RV length (TAPSE) versus developed force (PASP) [ 19 , 21 ].…”
Section: Discussionmentioning
confidence: 99%